Primary chronic adrenal insufficiency of autoimmune etiology. Review of the literature on a case - Sánchez Sánchez. , Samuel; Morales Madrigal, Miguel; Bouza Jiménez., Yanelka (Revista Universidad de Guayaquil, 2017)
The incidence of adrenal insufficiency is 1: 100 000. The primary causes are rarer, barely constitute 40% and are frequently linked to infectious diseases or autoimmune etiology. The objective is to describe the presentation of a case of primary chronic adrenal insufficiency of autoimmune etiology diagnosed in the General Hospital of Cienfuegos. Patient of 25 years, comes for abdominal pain. During the examination he reported a change in skin color and episodes of hypoglycemia. It is hypotensive. The complementary ones gave light hyponatremia. Subsequent study showed elevated ACTH and low Cortisol. Rest of the blood and imaging tests without alteration. The patient is under medication and followed up by consultation. Without complications.